The Contributions of Motor Skill Proficiency to Cognitive and Social Development in Early Childhood - Capio, Catherine M (Archīum Ateneo, 2024)
With limited evidence from intervention studies, causal relationships between motor competence and cognitive and social development have yet to be clearly established. In this research, we investigated whether a targeted training programme to improve fundamental movement skills (i.e., object control, locomotor) in young children would also lead to improvements in the cognitive (i.e., executive function) and social (i.e., socioemotional competence) domains. Using a two-arm group randomised intervention design, 185 children aged 36 to 60 months (mean 47.51, SD 8.11 months) were allocated to a motor skill intervention group or an active control group. The intervention was implemented over one school year, and outcomes were monitored across five time points. Longitudinal analysis was performed using hierarchical linear mixed-effects and latent growth curve models. Participation in the motor skill intervention led to higher rates of development of object control skills (p < 0.001) and executive function (p < 0.001). A dose‒response relationship was found in which those children who displayed greater development of object control skills over time also displayed greater development of executive function (p = 0.001). We found no significant effects of the intervention on locomotor skills, social behaviours, or socioemotional competence. These findings provide evidence of a causal relationship between motor and cognitive development.